Enrichment of Artemia Nauplii with bacteria grown in high C/N ratio, carbon source-microalgae media - Mallawaarachchi, Jayanthi Chandani; Md Yusoff, Fatimah; Khaw, Yam Sim; Zulperi, Zarirah; Md Yasin, Inasalwany (Asian Fisheries Society, 2024)
The microalgae-bacteria interaction in enriched culture media could affect the growth and nutritional properties of Artemia. The addition of carbon sources to the media improves the heterotrophic bacterial population, which in turn interacts with microalgae to improve the health and production of Artemia. The aim of this study was to assess the impacts of the microbial consortium developed with different fermented carbon sources and microalgae on Artemia. Three different microalgae, Chlorella sp./A1, Nannochloropsis oceanica/A2 and Chaetoceros calcitrans/A3 were mixed with three fermented carbon sources (rice bran/C1, tapioca flour/C2 and molasses/C3) to produce nine treatments (A1C1, A1C2, A1C3, A2C1, A2C2, A2C3, A3C1, A3C2, A3C3) and three controls with microalgae alone (A1, A2, A3). Enrichment was carried out for 24 h with Artemia instar I at an initial density of 25 individuals mL-1. Two-way ANOVA revealed that the survival, length, protein and lipid contents of Artemia nauplii were significantly affected (P < 0.05) by carbon source and species of microalgae. The carbon source–microalgae interaction also significantly affects Artemia survival, length, biomass and protein content. This study illustrated that bacteria associated with different carbon sources and microalgae consortia improved Artemia growth, survival, protein and lipid content.